RELIGIOUS HARMONIZATION ON ETHNO-RELIGIOUS COMMUNITIES OF MUSLIM AND DAYAK KATAB-KEBAHAN IN TEBING KARANGAN VILLAGE, MELAWI DISTRICT, WEST KALIMANTAN - Wendi Parwanto; Sahri Sahri; Sarah Busyra; Riyani Riyani; Syarifah Nadhiya (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2022)
Research on the Katab-Kebahan community or ethnic has been carried out by several researchers. In general, the research that has been done is narrative-descriptive in nature. Thus, the research has not studied the aspects of religious tolerance and moderation in the reality of the Katab-Kebahan community or ethnic between its Muslims and Dayaks. The purpose of this study is to describe religious harmonization in the Katab-Kebahan Muslim and Dayak ethnicities in the rural communities of Melawi, as well as uncover the factors that stimulate the formation of harmonization between them. The locus of this research is in the Tebing Karangan village, Melawi district, West Kalimantan. Meanwhile, the type of research is field research using a narrative-analytical model which also includes the archaeo-genealogical theory by Michel Foucault. The conclusion of this article explains that, basically, religious harmonization is formed from tolerance. But tolerance is formed through the process and various factors that support it. Such as the similarity in the vision and mission of life, the intensity of social-community relations, and the sense of kinship and togetherness that has been cultivated for a long time. This stimulates the emergence of a sense of mutual ownership and protection of one another.